DYNAMICS OF PROFESSIONAL DEVELOPMENT OF IT-SPECIALISTS - Ситник, В. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article presents the results of an empirical study of 72 people who study and work in the field of information technology. Twenty-six people are employees of an IT company having the experience of three to eight years, and forty-six people are undergraduate students of computer science department of Karazin National University. The gender structure of the respondents was approximately the same – 35 women, 37 men. Such factors of specialists professional success as socio-psychological, cognitive (level of creativity, causometry), motivational (socio-psychological instructions) and emotional (level of anxiety and overcoming stress) were studied. Reliable levels of anxiety, perceptions of team climate and creativity depending on the status of the professional were defined